Fitting analysis of the curve of main inclined section of surface subsidence of insufficient mining - Du, Wei; Guo, Ming; Lai, Jia; Zhang, Yang; Ma, Yafei; Dun, Huoda; Jia, Boyuan; Feng, Libiao; Li, Zhiqiang (Frontiers in Earth Science, 2025)
Based on the measured subsidence data of the 112,201 working face in Xiaobaodang Coal Mine of Shaanxi Province, the traditional probability integral method and probability density function method are used to study the curve fitting of the main inclined section under insufficient mining conditions. The analysis results show that the fitting effect of the probability density function method is better than that of the probability integral method. In view of the poor effect of edge fitting, the idea of sub-region fitting is proposed. Two sets of predicted parameters are used to fit the edge and central regions. The fitting results are close to the surface deformation, and the fitting effect is better. The method can improve the accuracy of surface deformation prediction. The research results can provide a reference for the prediction of surface subsidence in Xiaobaodang Coal Mine and its surrounding mining areas.